Case reportTranscatheter closure of patent foramen ovale with the use of the transseptal puncture - Kępka, Cezary; Rużyłło, Witold; Demkow, Marcin; Konka, Marek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2010)
Transcatheter patent foramen ovale closure became one of the routinely performed procedure in clinical practice. Despite this, in some patients, due to unfavorable anatomy and tunnel-like foramen passing through the interatrial septum with diagnostic catheter cannot be possible. In this report we present the case of successful implantation of Amplatzer PFO Occluder with the use of transseptal puncture technique.